"Fotoquímica “verde”: desenvolvimento de complexos de metais de transição luminescentes para ativação de oxigênio singleto e a sua aplicação na desinfecção de água contaminada com microorganismos patogênicos (Escherichia Coli e Enterococcus Faecalis)” - Maia, Paulo José de Sousa (Universidade Federal de São Carlos, 2015)
Green Photochemistry: Development of transition metal complexes for activation of luminescent singlet oxygen and its application in the disinfection of wastewaters contaminated with pathogenic microorganisms (Escherichia coli and Enterococcus faecalis). The development of the perylenes derivatives complexes Ru (II) and Re (I) has received increasing attention in energy transfer. Here in we investigated, the synthesis, characterization, energy transfer studies and biological testing of three complexes of Ru (II) and Re (I) cis-RuCl2(PDI1)2, cis-RuCl2(1,10- phen)(PDI1 ), fac-[Re(CO)3(PDI1)Br] and [Ru(1,10-phen)2(PDI2)]2+. The complexes are simple and stable preparation of both solid as well as DMSO solution (in the absence and presence of light) and are resistant to hydrolysis at pH 4 to 8. All compounds were characterized by 1H NMR, IV, elemental analysis and theoretical calculations whose results were consistent with the proposed structural. The complexes exhibit intense absorption in the visible region (500 nm, ε = 20,000 mol-1Lcm-1) and an intense band emission around 600nm, long emission lifetime 500 nsec and a small Stokes shift (600 cm-1), consistent with the rigid structure of the perylene chromophore. We observed that some complexes have paramagnetism ability in the ground state and both solution and on solid medium which was confirmed by RPE and theoretical calculation. These complexes were not able to produce photochemical 1O2. However, [Ru(1,10-phen)2(PDI2)]2+ presented photochemical generation of 1O2 dissolved in methanol, ethanol, acetone and acetonitrile and quantum yield of the formation of this species (Φ1O2) in order 0.30. Thus, we immobilize this complex on silica gel functionalized with aminopropyl group and it produced 1O2 with Φ1O2 around 0.20. The ability microbicide of these complexes were tested against the yeast Candida and values obtained show they are toxic for these microorganisms. These results lead us to believe that the complex can act on wastewater treatment.
Green photochemistry: development of transition metal complexes for activation of luminescent singlet oxygen and its application in the disinfection of wastewaters contaminated with pathogenic microorganisms (Escherichia coli and Enterococcus faecalis)
Keywords: Transferência de energia; Derivados de perileno; Levedura cândida; Energy tranfer; Perylenes derivative; Yeast Candida; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA INORGANICA::FISICO QUIMICA INORGANICA